2009
DOI: 10.2320/matertrans.mra2008481
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Hydrogen Absorption and Corrosion Behavior of Ti-6Al-4V Alloy Immersed in Acidic Fluoride Solutions

Abstract: The relationship between hydrogen absorption and the corrosion behavior of Ti-6Al-4V alloy has been examined by immersing the alloy in acidulated phosphate fluoride (APF) solution with various concentrations. Upon immersion in 0.1 mass% APF solution, no hydrogen absorption is observed despite the occurrence of general corrosion. In 0.2% APF solution, slight hydrogen absorption occurs soon after immersion, and then the surface of the specimen becomes uniformly covered with a crystalline corrosion product (Na 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In addition, when titanium components were used under hydrogenation environments, such as seawater, their service life would usually be determined by their corrosion resistance. However, current researches generally focused on the extremely acidic mediums such as nitric, sulfuric, and hydrochloric acid, [16][17][18][19][20] but rarely involve saline medium such as NaCl solution. [21] Meanwhile, as the components continue to work in those saline mediums, the dissociated hydrogen would constantly adsorb and react with titanium on the surface of these components, resulting in changes in their corrosion resistance, DOI: 10.1002/adem.201901182…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when titanium components were used under hydrogenation environments, such as seawater, their service life would usually be determined by their corrosion resistance. However, current researches generally focused on the extremely acidic mediums such as nitric, sulfuric, and hydrochloric acid, [16][17][18][19][20] but rarely involve saline medium such as NaCl solution. [21] Meanwhile, as the components continue to work in those saline mediums, the dissociated hydrogen would constantly adsorb and react with titanium on the surface of these components, resulting in changes in their corrosion resistance, DOI: 10.1002/adem.201901182…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research activity on Ti alloys and HF acid and F (fluoride) has been peripheral to the oilfield industry (Affrossman et al 2001;Al-Mayouf et al 2004;Fujita et al 2009;Rosalbino et al 2012;Divi and Grauman 2013), and even fewer studies can be identified addressing this topic within the industry publications (Schutz 2001;Baxter et al 2007;Pascarella and Reyes 2014). Offshore and deepwater assets are among the most intricate facilities in the oil and gas industry.…”
Section: Introductionmentioning
confidence: 99%
“…While the final equilibrium state of the dissolution (oxidation) products is typically titanium hexafluoride and pentafluoride, kinetically there are different species involved in the anodic process (Ti ϩ , Ti 2ϩ , Ti 3ϩ ) (Sutter and Goetz-Grandmont 1990;Fujita et al 2009;Fasmin et al 2015). It needs to be considered that the electrochemical steps are occurring in a heterogeneous medium-the metal surface immersed in a complex electrolyte-further complicating the anodic/cathodic processes (Hua et al 2004;Kong 2010).…”
Section: Introductionmentioning
confidence: 99%